2007
DOI: 10.1093/molbev/msm171
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Essential Design Features in Coiled Coil Silks

Abstract: Silks are strong protein fibers produced by a broad array of spiders and insects. The vast majority of known silks are large, repetitive proteins assembled into extended beta-sheet structures. Honeybees, however, have found a radically different evolutionary solution to the need for a building material. The 4 fibrous proteins of honeybee silk are small ( approximately 30 kDa each) and nonrepetitive and adopt a coiled coil structure. We examined silks from the 3 superfamilies of the Aculeata (Hymenoptera: Apocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
81
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 24 publications
4
81
0
Order By: Relevance
“…Sutherland et al (2006) were able to identify the coiled-coil silk sequences from silk gland cDNA libraries from European A. mellifera and determined the amino acid sequence of the coiled-coils. Sutherland et al (2007) confirmed that honeybee silk is formed from four coiled-coil proteins (fibroins), as originally suggested by Rudall (1962Rudall ( , 1965 on the basis of his X-ray diffraction data. The fibroin proteins contained extensive coiled-coil regions of conserved length flanked by largely unstructured termini.…”
Section: Honeybee Silk: An A-helical Silk and A Coiled-coil Proteinsupporting
confidence: 69%
See 4 more Smart Citations
“…Sutherland et al (2006) were able to identify the coiled-coil silk sequences from silk gland cDNA libraries from European A. mellifera and determined the amino acid sequence of the coiled-coils. Sutherland et al (2007) confirmed that honeybee silk is formed from four coiled-coil proteins (fibroins), as originally suggested by Rudall (1962Rudall ( , 1965 on the basis of his X-ray diffraction data. The fibroin proteins contained extensive coiled-coil regions of conserved length flanked by largely unstructured termini.…”
Section: Honeybee Silk: An A-helical Silk and A Coiled-coil Proteinsupporting
confidence: 69%
“…The patterns from honeybee silk fibres were considered most consistent with a four-strand coiled-coil structure with a tighter than expected super-helix radius of about 0.52 nm (Atkins 1967). In contrast, the dominant molecular structure in silk of other hymenopteran species is extended β-sheets (Warwicker 1960;Sutherland et al 2007) So, honeybee silk is an ά-helical fibroin (Rudall 1962), the micelles or crystallites of which form a four-stranded array of coiled-coils parallel to the fibre axis (Atkins 1967). Honeybee fibroin is crystalline relative to other insect silks (Lucas and Rudall 1968) while the hydrated fibre is only half as stiff as dry ones although they are equal in strength (Hepburn et al 1979).…”
Section: Honeybee Silk: An A-helical Proteinmentioning
confidence: 99%
See 3 more Smart Citations